Cryoresistance of Antarctic lichen Umbilicaria umbilicarioides Assessed by a Constant Rate Cooling Combined with Chlorophyll Fluorescence Data - Sekerák Jr , Jiří; Hájek, Josef; Puhovkin, Anton; Barták, Miloš (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):301